2018
DOI: 10.1016/j.soildyn.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain response of the LEAP-2015 centrifuge tests and numerical predictions

Abstract: The Liquefaction Experiments and Analysis Projects (LEAP) is an international effort to produce a set of high quality test data and then use it in a validation exercise of existing computational models and simulation procedures for soil liquefaction analysis. A validation effort (LEAP-GWU 2015) was undertaken using a benchmark centrifuge model of a sloping deposit tested in rigid-wall container. This article presents and discusses the shear stressstrain response and effective stress path of the LEAP-GW 2015 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Most of the modelers did include some of the recommended sensors. Zeghal et al [18] another article in this special issue) performed analysis to evaluate the effects of the side boundaries on the model behavior, and observed that the recordings from the recommended sensors in the arrays near the boundaries are generally consistent with anticipated boundary effects.…”
Section: Model Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the modelers did include some of the recommended sensors. Zeghal et al [18] another article in this special issue) performed analysis to evaluate the effects of the side boundaries on the model behavior, and observed that the recordings from the recommended sensors in the arrays near the boundaries are generally consistent with anticipated boundary effects.…”
Section: Model Geometrymentioning
confidence: 99%
“…The cyclic pore pressures at NCU and ZJU have a larger magnitude and are sharper than those measured at the other four centrifuge facilities. Zeghal et al [18] further analyze the pore pressure data and show that the cyclic pore pressures are affected by dilatancy and cyclic lateral stress associated with the rigid boundaries. Table 5 summarizes the time to liquefaction at P2 and, the number of cycles to liquefaction at P2 for Motion #2.…”
Section: A C H I E V E D M O T I O N S a N D D E V I A T I O N S F R mentioning
confidence: 99%
“…An anchoring frame beam is a very common form of support for reinforced slopes (Lin et al, 2017;Shi et al, 2019;Zheng et al, 2021b). Various research methods, such as theoretical analysis (Wang et al, 2020;Zeghal et al, 2018;Zhang S. et al, 2021;Zheng et al, 2021a), laboratory tests (Pan et al, 2020;Yao et al, 2020;Zhang et al, 2020b), numerical simulations (Ge et al, 2017), and on-site monitoring (Zhang et al, 2020a;Zhao et al, 2020) were used to study the mechanism and prevention of landslides. The physical model test is the most commonly used entity research method (Ghandil et al, 2016), which is widely used in many disciplines such as geotechnical, hydraulic, structure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…LEAP-2017 project is a sequel to the LEAP-2015 project (Kutter et al 2017;Manzari et al 2017;Zeghal et al 2017) that initiated an international collaboration for validation of constitutive and numerical modeling of soil liquefaction and its consequences using high-quality centrifuge tests. The goals of LEAP-2017 are to assess: (1) the repeatability and reproducibility of centrifuge tests, (2) the sensitivity of the experimental results to variation of testing parameters and conditions, and (3) the performance and validity of constitutive models and numerical modeling tools in predicting the observed response.…”
Section: Introductionmentioning
confidence: 99%